EXPLAINING ANIMAL GRIEF TO AUTISTIC CHILDREN - Aparecida Menegon, Michele (Health and Society, 2024)
The end of childhood, youth, the departure of a loved one from our home, the end of a loving relationship, the end of a phase, the loss of health, the end of a special friendship, are losses that often , we are not prepared to deal. When we talk about death, especially because our culture doesn’t talk much about this topic. Pain is something very subjective, meaning that everyone has an experience regarding what they lost in their life. Therefore, this topic needs to be talked about, in a broad way, but here, focusing on animal grief, which is even less talked about and little understood.